Ketogenic Diet for Epilepsy and Focal Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The efficacy and long-term treatment outcome of a classic ketogenic diet (KD) addon treatment (4:1 lipid/nonlipid ratio, without initial fasting and fluid restriction) were evaluated retrospectively in 47 children with intractable epilepsy and focal malformation of cortical development, in a study at Severance Children's and Sanggye Park Hospitals, Seoul, Korea.